Antibody Phage Display Methods and Protocols - O’Brien, Philippa M.; O’Brien, Philippa M.; Aitken, Robert.; Aitken, Robert. (Methods in Molecular Biology,, 2002)
Antibody phage display, the definitive technology for monoclonal production, has now advanced to a stage where it can be performed in nonspecialized research laboratories. In Antibody Phage Display: Methods and Protocols, Philippa M. O'Brien and Robert Aitken combine in one volume a comprehensive collection of established antibody phage display protocols, each accompanied by authoritative guidance that will enable the nonspecialist to carry them out successfully. Coverage spans the construction of antibody libraries, the selection of antibody clones with the desired properties, and their modification, expression, and purification. Each readily reproducible method is described by a hands-on expert in step-by-step detail and includes a wealth of practical advice not found in the scientific literature. Extensive notes discuss pitfalls to avoid and offer many possible alternative methods to suit special research situations. An overview by one of the world's leading experts in antibody phage display, Dr. Hennie R. Hoogenboom, surveys the current status of the field and the future of the technology. Comprehensive and highly practical, Antibody Phage Display: Methods and Protocols provides biochemists, molecular biologists, and immunologists with a gold-standard reference guide to the successful isolation, modification, and expression of recombinant antibodies using today's powerful phage display technology.